2019
DOI: 10.1177/0192513x19859612
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effects of Social Support on Psychological Health Through Self-Esteem in Emerging Adulthood

Abstract: Social constructivist theory suggests that social support affects internalizing and externalizing problems by improving self-esteem. The differential impact of these variables has not been fully explored between male and female genders. The current study examined how different sources of received or perceived social support from mother, father, or a close friend affect internalizing and externalizing problems as explained by self-esteem in emerging adulthood. Emerging adults attending college ( N = 854, ages 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Abundant research evidence has shown the effectiveness of social capital and social support in achieving stress relief among children and adults, whereas limited evidence exists among emerging adults (Szkody & McKinney, 2019) and college students (Yoo, 2018). Perceived social support has been negatively associated with stress in student samples (Jeong, 2019; Vats & Kaur, 2018) and it has been considered a buffer to stress and adversity (Southwick et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abundant research evidence has shown the effectiveness of social capital and social support in achieving stress relief among children and adults, whereas limited evidence exists among emerging adults (Szkody & McKinney, 2019) and college students (Yoo, 2018). Perceived social support has been negatively associated with stress in student samples (Jeong, 2019; Vats & Kaur, 2018) and it has been considered a buffer to stress and adversity (Southwick et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Those with a positive relationship with their parent (e.g., high disclosure, low conflict, and high support seeking behavior) may utilize parents as a base of support more often than an individual with a poor relationship with their parent (e.g., low disclosure, high conflict; Corry & Leavey, 2017). In addition, good relationships with parents are associated with a wide variety of positive health outcomes including better mental and physical overall health (e.g., Szkody & McKinney, 2019). Thus, in the current study we examined the influence of the two FCP orientations and family types (i.e., as assessed through latent profile analysis [LPA]) on these parent-child factors among emerging adults to address the gap in the literature.…”
Section: Parent-child Relationship Qualities and Help-seeking Behaviorsmentioning
confidence: 99%
“…However, few have examined how the perception of FCP influences child help-seeking behaviors and child help-providing behaviors in relation to the parent-child relationship. Examining the influence of FCP on parent-emerging adult relationship quality may shed light on how relationship quality and help/support seeking/providing behavior have been shown to be associated with various physical and mental health outcomes (e.g., Szkody & McKinney, 2019).…”
mentioning
confidence: 99%
“…Despite existing theories, the precise psychobiological pathways by which social support leads to health benefits and the factors that moderate and mediate this relationship are still not completely understood (DiMatteo, 2004; Gale, Kenyon, MacArthur, Jolly, & Hope, 2018; Szkody & McKinney, 2019; Baptista et al, 2020b; Wilson, Weiss, & Shook, 2020). To solve this gap research has mostly focused on the effects of social support in cardiovascular response to stress (Teoh & Hilmert, 2018), effects of social support in the neural system (Ditzen & Heinrichs, 2014; Eisenberger, Taylor, Gable, Hilmert & Lieberman, 2007; Morese, Lamm, Bosco, Valentini, & Silani, 2019) and immunologic responses (Pressman et al, 2005; Schrock et al, 2020).…”
Section: Concept Of Social Supportmentioning
confidence: 99%